History and historiography of linguistics : papers from the fourth International Conference on the History of the Language Sciences (ICHoLS IV) : Trier, 24-28 August 1987. II - Niederehe, Hans-Josef, 1937-; Koerner, E. F. K. (Amsterdam studies in the theory and history of linguistic science. Studies in the history of the language sciences, 1990)
Papers from the Fourth International Conference on the History of the Language Sciences (ICHoLS IV), Trier, 24-28 August, 1987.